1999
DOI: 10.1111/j.1745-459x.1999.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Analysis of Burgundy Pinot Noir Wines: A Comparison of Orthonasal and Retronasal Profiling

Abstract: Thirty Burgundy Pinot noir wines were evaluated by quantitative descriptive profile by nose (BN) and by mouth (BM) separately, by a trained panel composed of 12 judges. A specific vocabulary of 20 terms was developed. Sensory results were analyzed and compared by univariate and multivariate statistical techniques. Principal component analyses of the mean ratings BN and BM were fairly comparable regarding correlation among variables and the position of the wines. However, five sensory characteristics seem to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 22 publications
3
13
2
Order By: Relevance
“…Lawless 13 concluded that extended training failed to eliminate assessor difficulties in profiling complex aromas. However, with Burgundy Pinot Noir wines, Aubry et al 16 found more discriminant descriptors for aroma than oral attributes using identical vocabularies and training reference standards, unlike in this study.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Lawless 13 concluded that extended training failed to eliminate assessor difficulties in profiling complex aromas. However, with Burgundy Pinot Noir wines, Aubry et al 16 found more discriminant descriptors for aroma than oral attributes using identical vocabularies and training reference standards, unlike in this study.…”
Section: Discussioncontrasting
confidence: 51%
“…Aroma attributes, derived from a previous study 26 (16) were: pungent, floral, fruity (berries), fruity (tree fruits), spicy, vanilla, woody, green/black olive, grassy, yeasty, sulphury, caramelized, tar, rubbery, medicinal and musty ( Table 2). Training (Table 2) was for 5 days: 26 labelled standards were presented pairwise, then unlabelled standards were identified and wines showing specific characters used as illustrations.…”
Section: Experimental Wines and Sensory Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These tests showed that almost all descriptors chosen by the panel to describe the wine sample set were influenced by the wine treatments (Supplemental Tables 2, 3, and 4). Fewer significantly different aroma attributes were found, yet other researchers have reported good agreement between orthoand retronasal evaluation with slightly better discrimination by nose (Aubry et al 1999a(Aubry et al , 1999b. Wine aroma, detected orthonasally (by smell), and wine flavor, detected retronasally (in-mouth), depend on sensory active volatile compounds being detected by olfactory sensors located in the nasal cavity (Thorngate 1997).…”
Section: Resultsmentioning
confidence: 97%